Використання технології PON в концепції інтернет речей - Цилюрик, В. Е. (ХНУРЕ, 2019)
This paper is devoted to modern developments in the field of fiber-optic transmission lines used for systems of home devices that can perform actions and solve certain everyday tasks without human intervention. With the growing number of devices that are connected and controlled through the global network, the need for increased bandwidth for the Internet of Things is growing. In this paper, PON technology is considered as economically viable and satisfying all the needs of a smart home.